2020
DOI: 10.3390/jcm9123902
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for Cannabis Use to Treat Pain in Sickle Cell Disease

Abstract: Pain in Sickle Cell Disease (SCD) is a major comorbidity and unique with acute pain due to recurrent and episodic vaso-occlusive crises as well as chronic pain, which can span an individual’s entire life. Opioids are the mainstay treatment for pain in SCD. Due to recent health crises raised by adverse effects including deaths from opioid use, pain management in SCD is adversely affected. Cannabis and its products are most widely used for pain in multiple conditions and also by patients with SCD on their own. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 146 publications
0
7
0
Order By: Relevance
“…High‐quality randomized controlled studies evaluating the effects of cannabis on patients with SCD have not yet been conducted 163 . Results have been mixed as it relates to care utilization and pain outcomes.…”
Section: Substance Usementioning
confidence: 99%
See 1 more Smart Citation
“…High‐quality randomized controlled studies evaluating the effects of cannabis on patients with SCD have not yet been conducted 163 . Results have been mixed as it relates to care utilization and pain outcomes.…”
Section: Substance Usementioning
confidence: 99%
“…162 High-quality randomized controlled studies evaluating the effects of cannabis on patients with SCD have not yet been conducted. 163 Results have been mixed as it relates to care utilization and pain outcomes. A study of 72 patients' urine drug tests compared those who screened positive for cannabis (51%) with those who did not, and saw no difference in opioid use, fewer outpatient clinic appointments, but greater hospital admissions for VOC.…”
Section: Su Bsta Nce Usementioning
confidence: 99%
“…Retrospective studies have shown that 31% to 51% of people living with SCD self-report using cannabis, and the majority endorse using it for pain relief. 3 One retrospective study showed that medical cannabis use was associated with a decrease in hospital admissions. 4 In contrast, the only randomized controlled study of inhaled cannabis in SCD failed to show a significant decrease in pain ratings; this small study, however, showed a promising improvement in mood with cannabis.…”
Section: University Of Pittsburghmentioning
confidence: 99%
“…The review focused on 15 studies: one RCT, two cross-sectional surveys, three retrospective studies, one observational study, one qualitative study, one prospective study, one survey study, three case studies, and two questionnaire-based studies. While sample sizes, demographics, and other parameters differed for almost all these studies, one commonality was that further data is needed as well as long term studies ideally with less interference from other drugs to make decisive proposals on whether marijuana use is efficacious for pain relief in SCD or not [ 18 ].…”
Section: Reviewmentioning
confidence: 99%